Perancangan dan Implementasi Sistem Pemberdayaan Perempuan Untuk Meningkatkan Efisiensi Pencatatan dan Pelaporan Bantuan Perempuan Kepala Keluarga Menggunakan Metode Agile - Shintia Mutiarani; Agung Triayudi; Winarsih (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Women's empowerment is an effort to empower women to gain access to and control over resources, economic, political, social, cultural, so that women can organize themselves so as to be able to build capabilities and self-concept and ultimately improve the quality of life for women. Based on BPS data for 2020, the number of women who are heads of households in Indonesia is 11.44 million and some of them are at a low level of welfare. Meanwhile in Depok City, based on data from the Depok City Disdukcapil in 2020, there were 61,369 female family heads, 13,006 divorced and 48,363 divorced. In view of the significant increase in the number of PEKKA group members (Women headed households), of course it is not enough to manually record and manage this data, but there is a need for an information system that can facilitate data recording and recording as well as data analysis as information for policy making. The objectives of making the application for the empowerment of female heads of households include: Formation of a database for empowering women heads of households in sub-districts including their dependents, history of training, history of assistance, data on domestic violence, and other important data. Means of updating data on female heads of household members and their business activities heads of sub-district groups, Availability of promotional facilities for business products for women heads of households, Ease of access to information for PEKKA members